Neutrosophic BWM-TOPSIS Strategy under SVNS Environment - Surapati Pramanik; Suman Das; Rakhal Das; Binod Chandra Tripathy (Neutrosophic Sets and Systems, 2023)
Decision making under an uncertain environment is a critical task. In this article, we develop a Multi Attribute Decision Making (MADM) model using BWM and Neutrosophic-TOPSIS under Single Valued Neutrosophic Set (SVNS) environment. In developed model, BWM is utilized to find the weights of the attributes those are selected by a group of experts, and the Neutrosophic-TOPSIS is utilized to rank the alternatives.